2016
DOI: 10.1093/toxsci/kfw005
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Assessment of CoO and La2O3Metal Oxide Nanoparticles in Human Small Airway Epithelial Cells

Abstract: Cobalt monoxide (CoO) and lanthanum oxide (La2O3) nanoparticles are 2 metal oxide nanoparticles with different redox potentials according to their semiconductor properties. By utilizing these two nanoparticles, this study sought to determine how metal oxide nanoparticle’s mode of toxicological action is related to their physio-chemical properties in human small airway epithelial cells (SAEC). We investigated cellular toxicity, production of superoxide radicals and alterations in gene expression related to oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…CoO nanoparticles were purchased from SkySpring Nanomaterials (Houston, TX) and La 2 O 3 nanoparticles were purchased from Nanostructured & Amorphous Materials, Inc. (Houston, TX). The physicochemical characteristics of these particles are given in Table 1 [ 3 , 7 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…CoO nanoparticles were purchased from SkySpring Nanomaterials (Houston, TX) and La 2 O 3 nanoparticles were purchased from Nanostructured & Amorphous Materials, Inc. (Houston, TX). The physicochemical characteristics of these particles are given in Table 1 [ 3 , 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…We demonstrate that there are indeed differences in the pulmonary responses to CoO and La 2 O 3 nanoparticles in the induction of acute vs. chronic pulmonary responses. Such differences are reflective of adverse outcome pathways (AOPs) for these materials [ 11 ], which we previously established by our cellular and bolus aspiration studies [ 3 , 6 , 7 ]. The results of this inhalation study support the usefulness of a tiered approach including mechanistically relevant in vitro screening tests and bolus in vivo exposures in predicting pulmonary responses during inhalation exposures to nanoparticles [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this method, Rinna et al showed that silver ENMs activate mitogen-activated protein kinases such as ERK1/2 and JNK1/2 human epithelial embryonic cells [58]. Similarly, an increase in total tyrosine and threonine phosphorylation has been found in human small airway epithelial cells under exposure to both CoO and La 2 O 3 ENMs [59]. With the advances of MS-based proteomics, global phosphoproteome profiling now allows quantifying > 10,000 site-specific phosphorylation events in one experiment.…”
Section: Ms-based Ptm Profilingmentioning
confidence: 99%
“…This study will focus on a specific real-world LCPM: laser printer-emitted particles (PEPs) generated from nano-enabled toners which has been studied extensively by the authors and others over the last decade [18,19]. In US alone, 23 million printers are produced annually, and over 160,000 workers are employed in copier centers [20][21][22][23][24][25][26][27][28]. The new generation of toners contain ENPs, such as metals and metal oxides, and that PEPs with mode sizes of 49-208 nm are released during printing at concentrations of up to 1.3 million particles/cm 3 [15].…”
Section: Introductionmentioning
confidence: 99%